2006
DOI: 10.1111/j.1526-4610.2006.00310.x
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin Depletion, Cortical Spreading Depression, and Trigeminal Nociception

Abstract: Our findings indicate that 5-HT depletion enhances CSD-induced trigeminal nociception by increasing the cortical excitability and sensitivity of trigeminal nociceptive system. These findings may provide a better understanding regarding the relationship between low 5-HT and clinical headaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
72
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(75 citation statements)
references
References 14 publications
0
72
0
3
Order By: Relevance
“…There are at least 7 classes and 14 subtypes of 5-HT receptors, with varying biological effects. In general, the 5-HT 1 receptors mediate inhibitory neurotransmission, while the 5-HT [2][3][4][5][6][7] receptors mediate excitatory neurotransmission [4•]. In the brain, 5-HT is stored within synaptic vesicles, where it is protected from enzymatic degradation.…”
Section: The Serotonergic System and Cluster Headachementioning
confidence: 99%
See 1 more Smart Citation
“…There are at least 7 classes and 14 subtypes of 5-HT receptors, with varying biological effects. In general, the 5-HT 1 receptors mediate inhibitory neurotransmission, while the 5-HT [2][3][4][5][6][7] receptors mediate excitatory neurotransmission [4•]. In the brain, 5-HT is stored within synaptic vesicles, where it is protected from enzymatic degradation.…”
Section: The Serotonergic System and Cluster Headachementioning
confidence: 99%
“…Several studies conducted on the relation between migraine and serotonin metabolism [5] show low available levels of serotonin in the migrainous brain and a dysfunction of the brainstem serotonergic neurotransmission, which could act as a pain-triggering mechanism along the trigeminovascular pathway [6]. By contrast, only a few studies have been published on serotonin metabolism in patients with CH.…”
Section: The Serotonergic System and Cluster Headachementioning
confidence: 99%
“…First, pharmacological agents interacting with serotonin (5-HT) and/or its receptors are highly Neuropsychiatric Genetics effective in acute and prophylactic migraine treatment [The Subcutaneous Sumatriptan International Study Group, 1991;Hargreaves, 2007]. In addition, drugs known to facilitate 5-HT release are able to induce migraine attacks [Panconesi and Sicuteri, 1997] and low 5-HT blood levels predispose to cortical spreading depression (CSD) in rats [Supornsilpchai et al, 2006], the suggested upstream event of a migraine attack, particularly in MA [Moskowitz, 2007]. Although there is controversy, most studies point toward altered 5-HT levels in migraine patients both during attacks and interictally [Ferrari and Saxena, 1993;Hamel, 2007] and suggest that reduced 5-HT availability could be a fundamental event in migraine pathophysiology.…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesize that the migraine patients with paradoxical aggravation after the introduction of a new prophylactic drug had a paradoxical decrease in the CSD induction threshold. Mechanisms of such a decrease are unknown and are probably multifactorial, but it has been experimentally demonstrated that changes in serotonin neurotransmission modify cortical excitability and favour CSD [12]. …”
Section: Discussionmentioning
confidence: 99%